Development of Activated Carbon Fibers for Organic Removals - Alkathiri, Doaa Salim Samhan (2017)
A Master of Science thesis in Chemical Engineering by Doaa Salim Samhan Alkathiri entitled, "Development of Activated Carbon Fibers for Organic Removals," submitted in November 2017. Thesis advisor is Dr. Taleb Hassan Ibrahim and thesis co-advisor is Dr. Yehya Amin El Sayed. Soft and hard copy available.